A fast and simplified subglacial hydrological model for the Antarctic Ice Sheet and outlet glaciers - E. Kazmierczak; T. Gregov; T. Gregov; V. Coulon; F. Pattyn (The Cryosphere)
We present a novel and computationally efficient subglacial hydrological model that represents in a simplified way both hard- and soft-bed rheologies, as well as an automatic switch between efficient and inefficient subglacial discharge, designed for the Antarctic Ice Sheet. The subglacial model is dynamically linked to a regularized Coulomb friction law, allowing for a coupled evolution of the ice sheet on decadal to centennial timescales. It does not explicitly simulate the details of water conduits at the local scale and assumes that subglacial hydrology is in quasi-static equilibrium with the ice sheet, which makes the computations very fast. The hydrological model is tested on an idealized marine ice sheet and subsequently applied to the drainage basin of Thwaites Glacier, West Antarctica, that is composed of a heterogeneous (hard/soft) bed. We find that accounting for subglacial hydrology in the sliding law accelerates the grounding-line retreat of Thwaites Glacier under present-day climatic conditions. Highest retreat rates are obtained for hard-bed configurations and/or inefficient drainage systems. We show that the sensitivity is particularly driven by large gradients in effective pressure, more so than the value of effective pressure itself, in the vicinity of the grounding line. Therefore, we advocate for a better understanding of the subglacial system with respect to both the spatial and temporal variability in effective pressure and the rheological conditions/properties of the bed.